Harnessing Residents’ Practice-based Inquiries to Enhance Research Literacy: The Thoughtful Reading of Evidence into Clinical Settings (T-RECS) Initiative - Emmagene Worley; Edward H. Suh; Liliya Abrukin; Michael DeFilippo; Jonathan J. Kamler; Mahesh Polavarapu; Peter C. Wyer (Western Journal of Emergency Medicine, 2025)
Introduction: Research literacy is an important competency for all clinicians, but developing resident enthusiasm for it is difficult. At one academic emergency medicine (EM) residency program, we designed an innovative program to help residents improve literacy skills within a community of practice and use research literature to address clinical problems. Methods: A six-member faculty core team surveyed residents to assess their baseline experience with evidence-based medicine (EBM) and level of engagement with the medical literature. Interested residents joined an iterative curriculum development process that drew on previous EBM pedagogical experience and literacy theory. We developed a semi-structured approach that prioritizes using the reference frame of clinical applicability rather than research methodology. We held 90–120 minute sessions three times a year as part of the regular residency didactic conference; post-session evaluations with quantitative and qualitative elements were used to adjust subsequent didactics to refine the approach. Results: An average of 48 residents were in the EM training program during the nine sessions conducted during the study period. At baseline, residents had a high degree of exposure to EBM during medical school (94% of respondents) but low confidence in reading the medical literature (25%) or applying research to practice (10%). In contrast, they reported the novel program equipped them with skills to interpret literature and led to collective practice improvement. We found engagement was highest when residents led sessions based on inquiries that emerged out of their own training experience. Other positive factors included well-facilitated discussions between residents, relating questions to data-driven review of local practice patterns and addressing findings from free open access medical education (FOAMed) sources. The initial stages required significant team effort to design the pilot sessions, but later sessions were developed following the trajectory of resident inquiries using a minimally structured faculty consensus process and required less than 12 total faculty hours of commitment. Conclusion: An innovative program centered on residents’ practice-based queries of research literature appears to enhance learner enthusiasm for development of research literacy. Further development is needed to validate the overall effectiveness and generalizability of this approach.